Techniques and principles in language teaching - Larsen-Freeman, Diane (Oxford University Press, 2000)
This book provides a practical overview of the most important methods in the field. Readers are drawn into classrooms where various teaching methods and approaches are being used. They are encouraged to reflect on their own beliefs and to develop their own approach to language teaching.